Thermally buffered microhabitats recovery in tropical secondary forests following land abandonment. (September 2016) - González del Pliego, Pamela; Scheffers, Brett R.; Basham, Edmund W.; Woodcock, Paul; Wheeler, Charlotte; Gilroy, James J.; Medina Uribe, Claudia A.; Haugaasen, Torbjørn; Freckleton, Rob P.; Edwards, David P.
Abstract: Given the dramatic loss of tropical forests and accelerating climate change, secondary forest regeneration is increasingly recognised as being an important method for reversing losses in biodiversity and carbon stocks. The recolonisation of biodiversity within secondary forests depends in part upon the recovery of forest structure, including the range of microhabitats used by diverse local communities. Here, we investigate the return of critical microhabitats along a successional gradient of secondary forest in the Tropical Andes of Colombia. We measured the abundance of live (bromeliads, tree ferns and moss) and dead (deadwood and leaf litter) microhabitats across three landscapes, each encompassing primary, and young (4–18 yr old) and old secondary forests (19–35 yr old). Considering the increasing rate of climate warming in the region, we also explored whether these microhabitats provide thermally buffered microclimates. We found that secondary forests have different composition and lower complexity of microhabitats than primary forests, but microhabitats appear to be recovering towards primary forest levels. Furthermore, in all forest types, microhabitats had lower maximum temperatures and higher minimum temperatures, thereby serving as thermal buffers that reduced exposure to extreme temperatures. These benefits exist despite ambient temperatures in secondary forests surpassing those of primary forests by 1–2 °C on average. The protection of secondary forest and promotion of further forest regrowth in the Tropical Andes should represent an urgent investment for conservation, and the value of these forests for offering critical microhabitats and buffered microclimates under climate change should not be overlooked. Highlights: We assessed the recovery of microhabitats in tropical secondary forests. Microhabitats are regarded as mechanisms for fauna recovery in secondary forests. Microhabitat abundance and complexity recover as secondary forests mature. Microhabitats act as thermal buffers by reducing exposure to extreme temperatures. This buffering effect is present across all ages of secondary forests.